Amblyomma cajennense - (Fabricius, 1787) (Acari: Ixodiae): estudo da partenogênese sob condições controladas - Carolina Maria Vianna de Freitas (2000)
Some reproductive aspects of the adult stage of Amblyomma cajennense were studied. The capacity of virgin female to reproduce by parthenogenesis was evaluated, after experimental infestations without males in na equine in a limited and not limited site and, in a rabbit under controlled conditions. Moreover, the possibility of off host mating between virgin female and prefed males, was also evaluated. Females that engorged in both experiments, showed extended feed period and reduce engorgement weight in comparasion with those that were inseminated on host. Some of this unmated on or off host females, produced few sterile few eggs masses. Othewise, female that copulated on host, produced higher amount of eggs, which developed to viable larva. Under these conditions, females of A. cajemense were not able to reproduce by either parthenogenesis or after mating off host.